The Possible Role of Helicobacter pylori Infection in Hashimoto’s Thyroiditis - Hamid, Zainab A. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Autoimmune thyroiditis is one of autoimmune thyroid diseases. The cause of Hashimoto’s thyroiditis is not clearly identified; however, both genetic and environmental are suggested to play a role in pathogenesis of the disease. Helicobacter pylori (H pylori) is one of the possible causative agents. Objectives: The aim of this study is to look for the association of H. pylori infection with Hashimoto’s thyroiditis. Patients and Methods: a case-control study involved patients with Hashimoto’s thyroiditis (n=100) and control group (hyperthyroidism n=50, healthy persons n=50), the study groups were subjected to serological investigation of anti- H. pyloriIgG antibodies, anti-thyroid peroxidase antibody, and anti-thyroglobulin antibody(anti-TG Ab) using ELISA technique; besides, demographic data were collected from study groups. Results: Eighty two percent of Hashimoto’s thyroiditis patients were females; 57% of Hashimoto’s thyroiditis patients were positive for anti- H. pyloriIgG antibodies while the positive result was detected in only 22% of control group and the results were statistically significant (p <0.05). The strength and direction of the relationship between the concentrations of anti-HP IgGAbs and anti-TPO antibodies in Hashimoto’s thyroiditis group revealed positive correlation (r = 0.6241). Conclusion: the infection with H. pylori is one of the possible predisposing factors to etiology Hashimoto’s thyroiditis. The association between H. pylori infection and other genetic and environmental factors that are related to Hashimoto’s thyroiditis should be studied in depth.